2015
DOI: 10.1073/pnas.1417797112
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobial peptidase HrrP cleaves host-encoded signaling peptides and mediates symbiotic compatibility

Abstract: Legume-rhizobium pairs are often observed that produce symbiotic root nodules but fail to fix nitrogen. Using the Sinorhizobium meliloti and Medicago truncatula symbiotic system, we previously described several naturally occurring accessory plasmids capable of disrupting the late stages of nodule development while enhancing bacterial proliferation within the nodule. We report here that host range restriction peptidase (hrrP), a gene found on one of these plasmids, is capable of conferring both these properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
128
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(138 citation statements)
references
References 30 publications
(30 reference statements)
5
128
5
Order By: Relevance
“…In an accompanying report, Horváth et al (28) identified M. truncatula DNF7 encoding NCR169, suggesting that more than one NCR peptide can be indispensable for the nitrogen-fixing symbiosis. In another companion study, Price et al (29) recovered a rhizobial peptidase capable of degrading host NCR peptides. This collection of discoveries demonstrates the evolving nature in controlling bacterial differentiation in classical host-microbe mutualism.…”
Section: Discussionmentioning
confidence: 99%
“…In an accompanying report, Horváth et al (28) identified M. truncatula DNF7 encoding NCR169, suggesting that more than one NCR peptide can be indispensable for the nitrogen-fixing symbiosis. In another companion study, Price et al (29) recovered a rhizobial peptidase capable of degrading host NCR peptides. This collection of discoveries demonstrates the evolving nature in controlling bacterial differentiation in classical host-microbe mutualism.…”
Section: Discussionmentioning
confidence: 99%
“…Rhizobial factors such as NCR-degrading host-range restriction peptidases (HrrPs) play roles in late-stage compatibility (21). We suspected that the symbiotic effects of the NFS1 alleles might be altered by expressing in Rm41 the HrrP peptidase from S. meliloti B800 (21).…”
Section: Significancementioning
confidence: 99%
“…This region encompasses, among other genes, Medtr8g465280, which encodes an NCR peptide (17). Because NCRs have been shown to be host effectors that mediate terminal bacteroid differentiation required for nitrogen fixation in the Medicago-Sinorhizobium symbiosis (18,19,(22)(23)(24), we postulated that Medtr8g465280 was a candidate gene of NFS2.…”
mentioning
confidence: 99%